HUBUNGAN KETRAMPILAN SELF-REGULATED LEARNING DENGAN HASIL BELAJAR SISWA (STUDI META ANALISIS) - Ameliasari Tauresia Kesuma, S.E., M.Pd. (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2021)
The Self-regulated learning Relator to How Students Manage Their Own Learning Time, Thereby Improving Their Learning Result. There have been innumerable studies regarding the effectiveness of strategies in improving students’ performance, however most of them only looked at and emphasized on the students’ characters rather than the learning results. This study was aimed to find out how strong the correlation between the self-regulated learning and the learning result is. Meta analysis was used here. Data was collected by documenting articles of study results from various sources obtained through google.com search engine. Those articles have been published since 2010 up to 2019, and mostly related the self-regulated learning and learning performance. This study used an analysis design of fixed effect model with corrected effect size. The analysis was conducted with the help of JASP software by counting the correlation, drawing the forest plot, as well as the publication bias. The analysis results showed that there was a significant correlation between the self-regulated learning and the learning result.